The Influence Of Islamic Parenting Patterns and Parents Religious Understanding On Children’s Spiritual Intelligence In Muslim Families In Metro City - Rohmat, Rohmat; Yusuf, Muhammad; Fathurrohman, Amang; Choirudin, Choirudin (Assyfa Journal of Islamic Studies, 2024)
Islamic parenting faces significant challenges in the modern context, especially with the influence of technology that can divert children's attention from religious practices. This study aims to explore the influence of Islamic parenting and parental religious understanding on the spiritual intelligence of children in Muslim families in Metro City. The method used is quantitative, with the population being Muslim parents who have children aged 5-9 years. The sampling technique used is proportional stratified random sampling, with a total sample of 100 individuals. Data were collected through questionnaires and analyzed using multiple linear regression. The results of the study show that Islamic parenting has a significant effect on children's spiritual intelligence. This study also found that parents' religious understanding significantly contributes to the development of children's spiritual intelligence. Regression analysis results indicate that Islamic parenting and religious understanding together positively influence children's spiritual intelligence, with the regression equation ȳ = 23.576 + 0.223X1 + 0.452X2.